Oral contraceptive use and ovarian cancer risk for BRCA1/2 mutation carriers: an international cohort study - Schrijver, Lieske H; Antoniou, Antonis C; Olsson, Håkan; Mooij, Thea M; Roos-Blom, Marie-José; Azarang, Leyla; Adlard, Julian; Ahmed, Munaza; Barrowdale, Daniel; Davidson, Rosemarie; Donaldson, Alan; Eeles, Ros; et al. (American journal of obstetrics and gynecology, 2021)
BACKGROUND: Ovarian cancer risk in BRCA1 and BRCA2 mutation carriers has been shown to decrease with longer duration of oral contraceptive use. Although the effects of using oral contraceptives in the general population are well established (approximately 50% risk reduction in ovarian cancer), the estimated risk reduction in mutation carriers is much less precise because of potential bias and small sample sizes. In addition, only a few studies on oral contraceptive use have examined the associations of duration of use, time since last use, starting age, and calendar year of start with risk of ovarian cancer. OBJECTIVE: This study aimed to investigate in more detail the associations of various characteristics of oral contraceptive use and risk of ovarian cancer, to provide healthcare providers and carriers with better risk estimates. STUDY DESIGN: In this international retrospective study, ovarian cancer risk associations were assessed using oral contraceptives data on 3989 BRCA1 and 2445 BRCA2 mutation carriers. Age-dependent-weighted Cox regression analyses were stratified by study and birth cohort and included breast cancer diagnosis as a covariate. To minimize survival bias, analyses were left truncated at 5 years before baseline questionnaire. Separate analyses were conducted for each aspect of oral contraceptive use and in a multivariate analysis, including all these aspects. In addition, the analysis of duration of oral contraceptive use was stratified by recency of use. RESULTS: Oral contraceptives were less often used by mutation carriers who were diagnosed with ovarian cancer (ever use: 58.6% for BRCA1 and 53.5% BRCA2) than by unaffected carriers (ever use: 88.9% for BRCA1 and 80.7% for BRCA2). The median duration of use was 7 years for both BRCA1 and BRCA2 carriers who developed ovarian cancer and 9 and 8 years for unaffected BRCA1 and BRCA2 carriers with ovarian cancer, respectively. For BRCA1 mutation carriers, univariate analyses have shown that both a longer duration of oral contraceptive use and more recent oral contraceptive use were associated with a reduction in the risk of ovarian cancer. However, in multivariate analyses, including duration of use, age at first use, and time since last use, duration of oral contraceptive use proved to be the prominent protective factor (compared with <5 years: 5-9 years [hazard ratio, 0.67; 95% confidence interval, 0.40-1.12]; >10 years [hazard ratio, 0.37; 95% confidence interval, 0.19-0.73]; Ptrend=.008). The inverse association between duration of use and ovarian cancer risk persisted for more than 15 years (duration of ≥10 years; BRCA1 <15 years since last use [hazard ratio, 0.24; 95% confidence interval, 0.14-0.43]; BRCA1 >15 years since last use [hazard ratio, 0.56; 95% confidence interval, 0.18-0.59]). Univariate results for BRCA2 mutation carriers were similar but were inconclusive because of limited sample size. CONCLUSION: For BRCA1 mutation carriers, longer duration of oral contraceptive use is associated with a greater reduction in ovarian cancer risk, and the protection is long term.
Keywords: mutace; dospělí; BRCA1; nádory vaječníků; Europe; Female; Contraceptives, Oral; retrospective; Adult; ženské pohlaví; BRCA1 Protein; oral contraceptives; lidé; Evropa; Ovarian Neoplasms; Mutation; genetická predispozice k nemoci; následné studie; protein BRCA2; Genetic Predisposition to Disease; ovarian cancer; kohortové studie; epidemiology; observational; Cohort Studies; retrospektivní studie; proporcionální rizikové modely; Follow-Up Studies; Proportional Hazards Models; protein BRCA1; BRCA2; multivariate; kontraceptiva orální; lidé středního věku; risk; Retrospective Studies; survival bias; Middle Aged; BRCA2 Protein; Humans